Polarizing plate with retardation layer and image display device including same
By placing the resin film and the liquid crystal orientation curing layer in the polarizer with a phase difference layer, and adjusting the refractive index difference through the adhesive layer, the problems of dents and uneven interference during the bonding of the polarizer are solved, and better results are achieved image display effect.
Patent Information
- Application Number
- CN202411054940.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-02
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
When a polarizer with a phase difference layer is bonded to an image display panel, dents on the visual recognition side are prone to occur, and in the case of a multi-layer liquid crystal orientation curing layer, interference unevenness may become a problem, and the prior art is difficult to take into account both Suppress dents and interference inequality.
The polarizer including a polarizer is used to arrange the orientation curing layer of the liquid crystal compound, the resin film and another liquid crystal orientation curing layer in turn. The thickness of the resin film is 10 μm to 30 μm, and the adhesive layer is laminated with the phase difference layer to adjust the The difference in refractive index inhibits the occurrence of interference inequality and dents.
The generation of dents on the visual recognition side of the polarizer with a phase difference layer is effectively suppressed, and the suppression of interference is taken into account, providing better image display characteristics.
Smart Images

Figure CN119439351A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing plate with a phase difference layer and an image display device having the polarizing plate with a phase difference layer. Background Art
[0002] Image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (such as organic EL display devices and inorganic EL display devices) are rapidly becoming popular. In these image display devices, a polarizing plate with a phase difference layer is used for the purpose of improving display characteristics and preventing reflection. The polarizing plate with a phase difference layer can usually be laminated on the image display panel with the aid of an adhesive layer. A substrate and wiring are arranged on the surface of the image display panel.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2022-14611 Summary of the invention
[0006] Problems to be solved by the invention
[0007] When the polarizer with phase difference layer is attached to the image display panel, sometimes a dent is generated on the visual recognition side (i.e., the side not in contact with the image display panel) of the polarizer with phase difference layer. The thickness of the orientation solidified layer of the liquid crystal compound, i.e., the phase difference layer, is thinner than the phase difference layer of the resin film, so there is a tendency to easily produce dents. In addition, in the case of stacking more than two liquid crystal orientation solidified layers, i.e., the phase difference layer, interference unevenness may become a problem. It is known that an adhesive layer is configured between the phase difference layers in order to suppress interference unevenness. However, in the case of an adhesive layer, sometimes the dent becomes more significant. The main purpose of the present invention is to provide a polarizer with a phase difference layer that takes into account the suppression of interference unevenness and the suppression of dents.
[0008] Means for solving problems
[0009] 1. The polarizing plate with a phase difference layer according to an embodiment of the present invention comprises, in sequence: a polarizing plate including a polarizer, an orientation solidified layer of a liquid crystal compound, namely a first phase difference layer, a resin film, and a liquid crystal orientation solidified layer, namely a second phase difference layer, the slow axis of the first phase difference layer intersects with the slow axis of the second phase difference layer, the slow axis of the first phase difference layer intersects with the absorption axis of the polarizer, and the thickness of the resin film is 10 μm to 30 μm.
[0010] 2. In the polarizing plate with a retardation layer described in 1 above, the resin film may be laminated with the first retardation layer via a first adhesive layer, and the average refractive index n of the first adhesive layer is AD1 The average refractive index n of the above resin filmRF The following relationship is satisfied.
[0011] -0.03 <n AD1 -n RF <0.05
[0012] 3. In the polarizing plate with a retardation layer described in 1 or 2 above, the resin film may be laminated with the second retardation layer via a second adhesive layer, and the average refractive index n of the second adhesive layer is AD2 The average refractive index n of the above resin film RF The following relationship is satisfied.
[0013] -0.03 <n AD2 -n RF <0.05
[0014] 4. In the polarizing plate with a phase difference layer described in any one of 1 to 3 above, the resin film can be laminated with the first phase difference layer with the aid of a first adhesive layer, and the resin film can be laminated with the second phase difference layer with the aid of a second adhesive layer, and the total thickness of the first adhesive layer, the resin film and the second adhesive layer is 12 μm to 40 μm.
[0015] 5. In the polarizing plate with a retardation layer according to any one of 1 to 4 above, the resin film may be a cyclic olefin resin film or a cellulose resin film.
[0016] 6. In the polarizing plate with a retardation layer according to any one of 1 to 5 above, the resin film may have a refractive index distribution of nx=ny>nz.
[0017] 7. In the polarizing plate with phase difference layer described in any one of 1 to 6 above, Re(550) of the first phase difference layer is 200nm~300nm, and the angle formed by the slow axis of the first phase difference layer and the absorption axis of the polarizer can be 10°~20°, and Re(550) of the second phase difference layer is 100nm~190nm, and the angle formed by the slow axis of the second phase difference layer and the absorption axis of the polarizer can be 70°~80°.
[0018] 8. In the polarizing plate with a retardation layer according to any one of 2 to 7 above, the adhesive layer may be an adhesive layer.
[0019] 9. In another aspect of the embodiment of the present invention, an image display device is provided, wherein the image display device includes the polarizing plate with a phase difference layer according to any one of 1 to 8 above.
[0020] 10. The image display device described in 9 above may also be an organic electroluminescent display device.
[0021] Effects of the Invention
[0022] According to the embodiment of the present invention, a polarizing plate with a retardation layer in which the occurrence of interference unevenness and pits is suppressed can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic cross-sectional view of a polarizing plate with a retardation layer according to an embodiment of the present invention.
[0024] Figure 2 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to another embodiment of the present invention.
[0025] Description of Reference Numerals
[0026] 10 Polarizer
[0027] 11 Polarizer
[0028] 12. Protective layer
[0029] 13. Protective layer
[0030] 22 first bonding layer (adhesive layer)
[0031] 23 second bonding layer (adhesive layer)
[0032] 31. First phase difference layer
[0033] 32 Second phase difference layer
[0034] 41 first bonding layer (adhesive layer)
[0035] 42 second bonding layer (adhesive layer)
[0036] 50 Resin film
[0037] 60 Adhesive layer
[0038] 100 Polarizing film with phase difference layer DETAILED DESCRIPTION
[0039] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0040] (Definition of terms and symbols)
[0041] The definitions of terms and symbols in this specification are as follows.
[0042] (1) Refractive index (nx, ny, nz)
[0043] “nx” is the refractive index in the direction where the refractive index in the plane is maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0044] (2) In-plane phase difference (Re)
[0045] "Re(λ)" is the in-plane phase difference measured at 23°C using light of wavelength λnm. For example, "Re(550)" is the in-plane phase difference measured at 23°C using light of wavelength 550nm. Re(λ) is calculated by the formula: Re(λ) = (nx-ny) × d, when the thickness of the layer (thin film) is d (nm).
[0046] (3) Retardation in the thickness direction (Rth)
[0047] "Rth(λ)" is the phase difference in the thickness direction measured at 23°C using light of wavelength λnm. For example, "Rth(550)" is the phase difference in the thickness direction measured at 23°C using light of wavelength 550nm. Rth(λ) is calculated by the formula: Rth(λ) = (nx-nz) × d, when the thickness of the layer (film) is d (nm).
[0048] (4) Nz coefficient
[0049] The Nz coefficient is calculated by Nz=Rth / Re.
[0050] (5) Angle
[0051] When an angle is mentioned in this specification, the angle includes both clockwise and counterclockwise relative to a reference direction. Therefore, for example, "45°" means ±45°.
[0052] A. Overall structure of polarizing plate with phase difference layer
[0053] Figure 1It is a schematic cross-sectional view of a polarizer with a phase difference layer according to an embodiment of the present invention. The polarizer 100 with a phase difference layer shown in the figure has, in sequence: a polarizer 10 including a polarizer 11, an orientation solidification layer of a liquid crystal compound (hereinafter, also referred to as a liquid crystal orientation solidification layer), namely a first phase difference layer 31, a resin film 50, and a liquid crystal orientation solidification layer, namely a second phase difference layer 32. The polarizer 10 typically includes a polarizer 11 and protective layers 12 and 13 arranged on both sides of the polarizer 11. The protective layer 13 can also be omitted. For example, in the case where the phase difference layer can also function as a protective layer, the protective layer 13 can also be omitted. In the polarizer 100 with a phase difference layer, the slow axis of the first phase difference layer 31 intersects with the slow axis of the second phase difference layer 32, and the slow axis of the first phase difference layer 31 intersects with the absorption axis of the polarizer 11. For example, as described later, the angle between the slow axis of the first phase difference layer 31 and the absorption axis of the polarizer 11 may be 10° to 20°, and the angle between the slow axis of the second phase difference layer 32 and the absorption axis of the polarizer 11 may be 70° to 80°. The resin film 50 is preferably laminated on the first phase difference layer 31 with the aid of a first adhesive layer 41, and laminated on the second phase difference layer 32 with the aid of a second adhesive layer 42. In this specification, an adhesive layer refers to an adhesive layer or an adhesive layer. In the example shown in the figure, the resin film 50 is laminated on the first phase difference layer 31 with the aid of a first adhesive layer 41 as an adhesive layer, and laminated on the second phase difference layer 32 with the aid of a second adhesive layer 42 as an adhesive layer. Figure 2 It is a schematic cross-sectional view of a polarizer with a phase difference layer according to another embodiment of the present invention. In this example, the resin film 50 is preferably laminated with the first phase difference layer 31 by means of a first adhesive layer 22 as an adhesive layer, and laminated on the second phase difference layer 32 by means of a second adhesive layer 23 as an adhesive layer. The thickness of the resin film 50 is 10μm to 30μm. The thin thickness of the liquid crystal orientation solidification layer, i.e., the phase difference layer, can contribute to the thinning of the polarizer with the phase difference layer. On the other hand, the problem of dents when bonding to the liquid crystal panel may occur. In addition, in a polarizer with a phase difference layer including a plurality of liquid crystal orientation solidification layers, i.e., phase difference layers, the phase difference layer causes film interference, which may cause interference unevenness. As a method for eliminating interference unevenness, it is known, for example, to configure an adhesive layer between the liquid crystal orientation solidification layer, i.e., the phase difference layer. However, when an adhesive layer is configured, the generation of dents when bonding to the liquid crystal panel may become more significant. Therefore, it is difficult to take both the generation of dents and the suppression of interference unevenness into account. As described above, the polarizer with a phase difference layer according to the embodiment of the present invention is provided with a resin film having a thickness of 10 μm to 30 μm between the liquid crystal orientation solidification layer, i.e., the phase difference layer. If such a polarizer with a phase difference layer is provided, it is possible to provide a polarizer with a phase difference layer that can take into account both the suppression of the generation of dents and the suppression of interference unevenness, which has been difficult to achieve so far.
[0054] As described above, the resin film is preferably laminated with the first phase difference layer via the first adhesive layer. In this embodiment, the average refractive index n of the first adhesive layer is AD1 The average refractive index n of the resin film RF It is preferable to satisfy the following relationship. If the average refractive index n of the first adhesive layer is AD1 With the average refractive index n RF If the following relationship is satisfied, the interference unevenness can be further suppressed. The refractive index can be measured using an Abbe refractometer or a prism coupler at 25°C and 589nm. It should be noted that, regarding the refractive index of the adhesive layer, the adhesive used to form the adhesive layer is applied to any appropriate polymer film (such as a cycloolefin resin film) to form an adhesive layer (thickness 100μm), and then the polymer film is laminated on the adhesive layer to form a laminate (polymer film / adhesive layer / polymer film) for measurement. In this specification, the average refractive index refers to the average value of nx, ny, and nz.
[0055] -0.03 <n AD1 -n RF <0.05
[0056] As described above, the resin film is preferably laminated with the second phase difference layer via the second adhesive layer. AD2 The average refractive index n of the resin film RF It is preferable to satisfy the following relationship. If the average refractive index n of the second adhesive layer is AD2 With the average refractive index n RF If the following relationship is satisfied, interference unevenness can be further suppressed.
[0057] -0.03 <n AD2 -n RF <0.05
[0058] In one embodiment, the resin film is preferably laminated with the first phase difference layer by means of a first adhesive layer, and laminated with the second phase difference layer by means of a second adhesive layer. In this embodiment, the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is preferably 12 μm to 40 μm, more preferably 12 μm to 35 μm, and further preferably 15 μm to 30 μm. If the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is within the above range, the interference unevenness can be further suppressed. Furthermore, when the obtained polarizing plate with a phase difference layer is used in an image display device, a very excellent reflection hue can be achieved.
[0059] In addition to the first phase difference layer and the second phase difference layer, the polarizing plate with phase difference layer can further be provided with other phase difference layers. The other phase difference layer can be typically provided on the outside of the second phase difference layer 32 (the side opposite to the polarizer 10). The optical properties (such as refractive index properties, in-plane phase difference, Nz coefficient, photoelastic coefficient), thickness, configuration position, etc. of the other phase difference layers can be appropriately set according to the purpose. The refractive index properties of the other phase difference layers are typically such that the relationship nz>nx=ny is shown.
[0060] The polarizer 100 with a phase difference layer may have an adhesive layer 60 as the outermost layer. The polarizer 100 with a phase difference layer may be attached to an image display device (substantially an image display panel) by means of the adhesive layer 60. In practice, it is preferred that a release liner is temporarily bonded to the surface of the adhesive layer 60 until the polarizer with a phase difference layer is used. By temporarily bonding the release liner, the adhesive layer is protected until the actual use, and the roll-up of the polarizer with a phase difference layer is possible.
[0061] The thickness of the polarizer with a phase difference layer can be set to any appropriate value. In one embodiment, the total thickness of the polarizer with a phase difference layer is preferably less than 150 μm, more preferably less than 140 μm, further preferably less than 120 μm, more preferably less than 100 μm, further more preferably less than 90 μm, and particularly preferably less than 85 μm. The total thickness of the polarizer with a phase difference layer can be, for example, more than 30 μm. It should be noted that the total thickness of the polarizer with a phase difference layer refers to the total thickness of the polarizer, the phase difference layer, the resin film, and the adhesive layer for stacking them (that is, the total thickness of the polarizer with a phase difference layer does not include the thickness of the outermost adhesive layer, and the thickness of the release liner that can be temporarily bonded to the surface of the outermost adhesive layer).
[0062] Hereinafter, the components of the polarizing plate with a retardation layer will be described in more detail.
[0063] B. Polarizer
[0064] B-1. Polarizer
[0065] The polarizer is typically composed of a resin film containing a dichroic substance (typically iodine). As the resin film, any appropriate resin film that can be used as a polarizer can be used. The resin film is typically a polyvinyl alcohol resin (hereinafter referred to as "PVA resin") film. The resin film can be a single-layer resin film or a laminate of two or more layers.
[0066] As a specific example of a polarizer composed of a single-layer resin film, a polarizer in which a PVA-based resin film has been subjected to a dyeing treatment and a stretching treatment (representatively uniaxial stretching) using iodine can be cited. The above-mentioned dyeing using iodine is performed, for example, by immersing the PVA-based resin film in an iodine aqueous solution. The stretching ratio of the above-mentioned uniaxial stretching is preferably 3 to 7 times. Stretching can be performed after the dyeing treatment, or it can be performed while dyeing. In addition, dyeing can also be performed after stretching. As needed, the PVA-based resin film is subjected to a swelling treatment, a cross-linking treatment, a cleaning treatment, a drying treatment, etc. For example, by immersing the PVA-based resin film in water for washing before dyeing, not only can the dirt and anti-blocking agent on the surface of the PVA-based resin film be cleaned, but also the PVA-based resin film can be swelled to prevent uneven dyeing.
[0067] As a specific example of a polarizer obtained using a laminate, there can be cited a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be made, for example, in the following manner: a PVA-based resin solution is applied to a resin substrate, dried to form a PVA-based resin layer on the resin substrate, and a laminate of the resin substrate and the PVA-based resin layer is obtained; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In the present embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. Stretching typically includes immersing the laminate in a boric acid aqueous solution for stretching. Furthermore, the stretching may further include stretching the laminate in the air at a high temperature (e.g., above 95°C) before stretching in a boric acid aqueous solution as needed. Furthermore, in the present embodiment, it is preferred that the laminate is subjected to a drying shrinkage treatment in which the laminate is shrunk by more than 2% in the width direction by heating while being transported in the length direction. Typically, the manufacturing method of the present embodiment includes sequentially performing an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment on the laminate. By introducing auxiliary stretching, the crystallinity of the PVA can be improved even when the PVA is coated on the thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of the PVA in advance, when immersed in water in the subsequent dyeing process and the stretching process, problems such as the reduction and dissolution of the orientation of the PVA can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation and the reduction of the orientation of the polyvinyl alcohol molecules can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. Thus, the optical properties of the polarizer obtained by the treatment process of immersing the laminate in a liquid such as a dyeing treatment and an underwater stretching treatment can be improved. Furthermore, by shrinking the laminate in the width direction using a drying shrinkage treatment, the optical properties can be improved. The obtained laminate of resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective layer of polarizer), or the resin substrate can be peeled off from the laminate of resin substrate / polarizer, and any appropriate protective layer used according to the purpose can be stacked on the peeling surface for use. The details of the manufacturing method of such a polarizer are, for example, recorded in Japanese Patent Publication No. 2012-73580 (Japanese Patent No. 5414738) and Japanese Patent No. 6470455. For these publications, the entire records are cited in this specification as a reference.
[0068] The thickness of the polarizer is preferably 1 to 30 μm, more preferably 1 to 25 μm, further preferably 1 to 15 μm, further more preferably 1 to 10 μm, and particularly preferably 1 to 8 μm. If the thickness of the polarizer is within the above range, the polarizing plate with a retardation layer can be made thinner.
[0069] The polarizer preferably shows absorption dichroism at any wavelength between 380nm and 780nm. The single transmittance Ts of the polarizer is preferably 40% to 48%, more preferably 41% to 46%. The polarization degree P of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more. The above single transmittance is typically the Y value measured using an ultraviolet visible spectrophotometer and corrected for sensitivity. The above polarization degree is typically obtained by the following formula based on the parallel transmittance Tp and the orthogonal transmittance Tc measured using an ultraviolet visible spectrophotometer and corrected for sensitivity.
[0070] Polarization degree (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0071] B-2. Protective layer
[0072] The protective layers 12 and 13 are formed by any appropriate film that can be used as a protective layer of a polarizer. As a specific example of the material that becomes the main component of the film, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, polynorbornene resins, polyolefin resins, (meth) acrylic resins, acetate resins, etc. can be listed. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic resins, carbamate resins, (meth) acrylic acid carbamate resins, epoxy resins, silicone resins, etc. can also be listed. In addition, for example, glassy polymers such as siloxane polymers can also be listed. In addition, the polymer film described in Japanese Patent Publication No. 2001-343529 (WO 01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition having an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be listed. The polymer film can be, for example, an extrusion molding of the above resin composition.
[0073] The polarizing plate with a retardation layer is typically disposed on the visual recognition side of the image display device, and the protective layer 12 is typically disposed on the visual recognition side thereof. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coating, anti-reflection treatment, anti-sticking treatment, anti-glare treatment, etc. as needed.
[0074] The thickness of the protective layer is preferably 10 μm to 50 μm, more preferably 10 μm to 30 μm. When surface treatment is performed, the thickness of the outer protective layer (protective layer 12 ) is the thickness including the thickness of the surface treatment layer.
[0075] C. Phase difference layer
[0076] As described above, the first phase difference layer and the second phase difference layer are liquid crystal orientation solidification layers. In the case where the phase difference layer is a liquid crystal orientation solidification layer, the dents when attached to the image display panel can become more significant. In addition, interference unevenness caused by thin film interference of the liquid crystal orientation solidification layer may occur. As described above, in an embodiment of the present invention, a liquid crystal orientation solidification layer, i.e., a first phase difference layer, a resin film with a thickness of 10 μm to 30 μm, and a liquid crystal orientation solidification layer, i.e., a second phase difference layer, are sequentially provided. If a resin film with a thickness of 10 μm to 30 μm is stacked between the liquid crystal orientation solidification layer, i.e., the phase difference layer, the suppression of interference unevenness and the suppression of dents can be taken into account. The phase difference layer may further include an orientation film and / or a substrate. As described above, the slow axis of the first phase difference layer intersects with the absorption axis of the polarizer, and the slow axis of the first phase difference layer intersects with the slow axis of the second phase difference layer. The angle between the slow axis of the first phase difference layer and the absorption axis of the polarizer, and the angle between the slow axis of the first phase difference layer and the slow axis of the second phase difference layer can be set to any appropriate value according to the design. It should be noted that in this section, the first phase difference layer and the second phase difference layer are collectively referred to as phase difference layers. When it is necessary to distinguish the first phase difference layer from the second phase difference layer, "first" and "second" are written.
[0077] The first retardation layer preferably has a Re(550) of 200 nm to 300 nm, and the angle formed by the slow axis of the first retardation layer and the absorption axis of the polarizer is 10° to 20°. Additionally, the second retardation layer preferably has a Re(550) of 100 nm to 190 nm, and the angle formed by the slow axis of the second retardation layer and the absorption axis of the polarizer is 70° to 80°. In this embodiment, either the first retardation layer or the second retardation layer can function as a λ / 4 plate, and the other can function as a λ / 2 plate. For example, when the first retardation layer functions as a λ / 2 plate and the second retardation layer functions as a λ / 4 plate, the Re(550) of the first retardation layer is preferably 200 nm to 300 nm, more preferably 200 nm to 270 nm, further preferably 210 nm to 260 nm, and particularly preferably 230 nm to 260 nm. The Re(550) of the second retardation layer is preferably 100 nm to 200 nm, more preferably 100 nm to 170 nm, further preferably 110 nm to 150 nm, and particularly preferably 110 nm to 130 nm.
[0078] The thickness of the first retardation layer can be adjusted, for example, in a manner to obtain the desired in-plane retardation of the λ / 2 plate. The thickness of the first retardation layer is, for example, 2.0 μm to 4.0 μm. The thickness of the second retardation layer can be adjusted, for example, in a manner to obtain the desired in-plane retardation of the λ / 4 plate. The thickness of the second retardation layer is, for example, 0.5 μm to 2.5 μm.
[0079] In this embodiment, the angle formed by the slow axis of the first retardation layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably 12° to 16°. Additionally, the angle formed by the slow axis of the second retardation layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and further preferably 72° to 76°. In this embodiment, the first retardation layer and the second retardation layer can exhibit an inverse dispersion wavelength characteristic in which the phase difference value increases with the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the phase difference value decreases with the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the phase difference value hardly changes with the wavelength of the measurement light.
[0080] At least one of the first retardation layer and the second retardation layer typically exhibits a refractive index characteristic of the relationship nx > ny = nz. It should be noted that "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within the range that does not impair the effects of the present invention, it may sometimes be ny > nz or ny < nz. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3.
[0081] In this embodiment, as the above-mentioned liquid crystal compound used in the first phase difference layer and the second phase difference layer, for example, a liquid crystal compound (nematic liquid crystal) whose liquid crystal phase is a nematic phase can be cited. As such a liquid crystal compound, for example, a liquid crystal polymer or a liquid crystal monomer can be used. The liquid crystal performance mechanism of the liquid crystal compound can be either lyotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer can be used alone or in combination.
[0082] In the case where the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a cross-linkable monomer. This is because the orientation state of the liquid crystal monomer can be fixed by polymerizing or cross-linking (i.e., curing) the liquid crystal monomer. After the liquid crystal monomer is oriented, for example, if the liquid crystal monomers are polymerized or cross-linked with each other, the orientation state can be fixed. Here, polymers are formed by polymerization, and three-dimensional network structures are formed by cross-linking, but they are non-liquid crystal. Therefore, the phase difference layer formed will not undergo a transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes that are unique to liquid crystal compounds. As a result, the phase difference layer becomes a phase difference layer with extremely excellent stability that is not affected by temperature changes.
[0083] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its type. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and even more preferably 60°C to 90°C.
[0084] As the above-mentioned liquid crystal monomer, any appropriate liquid crystal monomer can be adopted. For example, the polymerizable mesogen compounds recorded in Japanese Patent Publication No. 2002-533742 (WO 00 / 37585), EP 358208 (US 5211877), EP 66137 (US 4388453), WO 93 / 22397, EP0261712, DE 19504224, DE 4408171 and GB 2280445 etc. can be used. As the specific example of such polymerizable mesogen compounds, for example, the trade name LC 242 of BASF, the trade name E7 of Merck, and the trade name LC-Sillicon-CC 3767 of Wacker-Chem can be listed. As the liquid crystal monomer, the nematic liquid crystal monomer is preferred. The specific example of the liquid crystal compound and the details of the formation method of the orientation solidified layer are as described above.
[0085] The case where the first phase difference layer functions as a λ / 2 plate and the second phase difference layer functions as a λ / 4 plate is described, but the first phase difference layer can also be used as a λ / 4 plate and the second phase difference layer can also be used as a λ / 2 plate. In addition, the above description describes the case where the angle between the slow axis of the first phase difference layer and the absorption axis of the polarizer is 10° to 20° (about 15°) and the angle between the slow axis of the second phase difference layer and the absorption axis of the polarizer is 60° to 80° (about 75°), but the angle between the slow axis of the first phase difference layer and the absorption axis of the polarizer can also be set to about 75° and the angle between the slow axis of the second phase difference layer and the absorption axis of the polarizer can also be set to about 15°.
[0086] D. Resin film
[0087] As a resin film, any appropriate resin film can be used. As described above, if a resin film is laminated between the first phase difference layer and the second phase difference layer by means of a first adhesive layer and a second adhesive layer, a polarizer with a phase difference layer in which interference unevenness and the generation of dents are suppressed can be provided. As a resin constituting a resin film, any appropriate resin can be used. For example, cyclic olefin resins such as norbornene resins, cellulose resins such as triacetyl cellulose resins, acrylic resins, polycarbonate resins, etc. can be listed. Preferably, cyclic olefin resins and cellulose resins are used. Resins can be used only one type, or two or more types can be used in combination. In addition, the resin film can be a single film or a laminate of more than two layers. The resin film is preferably unstretched (unstretched resin film).
[0088] The thickness of the resin film is 10 μm to 30 μm, preferably 10 μm to 25 μm, and more preferably 12 μm to 20 μm. When the thickness of the resin film is within the above range, the generation of interference unevenness and dents can be suppressed. As described above, in one embodiment, the thickness of the resin film can be adjusted so that the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is 10 μm to 30 μm.
[0089] The resin film may have any appropriate refractive index distribution. In one embodiment, the resin film may preferably be a so-called negative C plate having a refractive index distribution satisfying nx=ny>nz. If the resin film is a negative C plate, a polarizing plate with a phase difference layer having excellent image display properties can be provided.
[0090] The average refractive index of the resin film is n RF It can be set to any appropriate value. For example, as long as the average refractive index n of the first adhesive layer is AD1 With the average refractive index n RF and / or the average refractive index n of the second adhesive layer AD2 With the average refractive index n RFThe average refractive index n of the resin film can satisfy the above relationship. RF It is preferably 1.40 to 1.60, more preferably 1.45 to 1.55, and still more preferably 1.47 to 1.53. When the average refractive index of the resin film is within the above range, a polarizing plate with a retardation layer in which interference unevenness is further suppressed can be obtained.
[0091] The smaller the in-plane phase difference Re(550) of the resin film, the more preferred. The in-plane phase difference Re(550) of the resin film is preferably 20 nm or less, more preferably 15 nm or less, further preferably 10 nm or less, and particularly preferably 5 nm or less. If the in-plane phase difference Re(550) of the resin film is within the above range, a polarizing plate with a phase difference layer having excellent image display characteristics can be provided. The in-plane phase difference Re(550) is, for example, 0 nm or more.
[0092] The smaller the absolute value of the phase difference Rth (550) in the thickness direction of the resin film, the more preferred. The absolute value of the phase difference Rth (550) in the thickness direction of the resin film is preferably less than 20nm, more preferably less than 15nm, further preferably less than 10nm, and particularly preferably less than 5nm. If the absolute value of the phase difference Rth (550) in the thickness direction of the resin film is within the above range, a polarizing plate with a phase difference layer having excellent image display characteristics can be provided. The absolute value of the phase difference Rth (550) in the thickness direction is, for example, greater than 0nm.
[0093] The total light transmittance of the resin film is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. The total light transmittance of the resin film is, for example, 99% or less. If the total light transmittance of the resin film is within the above range, a polarizing plate with a phase difference layer having excellent image display properties can be provided. The total light transmittance of the resin film can be measured according to JIS K 7361.
[0094] The haze of the resin film is preferably 10% or less, more preferably 5% or less, further preferably 1% or less, and particularly preferably 0.5% or less. The haze is, for example, 0.1% or more. If the haze of the resin film is within the above range, a polarizing plate with a phase difference layer having excellent image display properties can be provided. The haze of the resin film can be measured according to JIS K 7361.
[0095] The tensile modulus of the resin film is preferably 1000 MPa to 3000 MPa, more preferably 1200 MPa to 2500 MPa, and further preferably 1500 MPa to 2000 MPa. If the tensile modulus of the resin film is within the above range, the generation of dents when attached to an image display panel can be suppressed. The tensile modulus of the resin film can be measured at room temperature (23° C.) according to JIS K 7161.
[0096] The tensile strength at break of the resin film is preferably 0.5N to 20N, more preferably 1N to 15N, and further preferably 3N to 12N. If the tensile strength at break of the resin film is within the above range, the generation of dents when attached to an image display panel can be suppressed. The tensile strength at break of the resin film can be measured at room temperature (23° C.) according to JIS K 7161.
[0097] The elongation at break of the resin film is preferably 1% to 10%, more preferably 2% to 8%, and further preferably 3% to 7%. If the elongation at break of the resin film is within the above range, the generation of dents when attached to an image display panel can be suppressed. The elongation at break of the resin film can be measured by using a thermomechanical analyzer (TMA).
[0098] The moisture permeability of the resin film is preferably 20 g / m 2 / 24 hours~60g / m 2 / 24 hours, more preferably 25g / m 2 / 24 hours~50g / m 2 / 24 hours, more preferably 30g / m 2 / 24 hours~40g / m 2 When the moisture permeability of the resin film is within the above range, the generation of dents when attached to an image display panel can be suppressed. The moisture permeability of the resin film can be measured under the conditions of a temperature of 40° C. and a humidity of 92% RH in accordance with JIS Z 0208.
[0099] E. Adhesive layer
[0100] As described above, the resin film is preferably laminated on the first phase difference film by means of a first adhesive layer, and laminated on the second phase difference layer by means of a second adhesive layer. As described above, the adhesive layer is an adhesive layer or an adhesive layer. In one embodiment, the adhesive layer is preferably an adhesive layer. If the adhesive layer is an adhesive layer, the generation of dents can be further suppressed. The average refractive index n of the first adhesive layer is AD1 and the average refractive index n of the second adhesive layer AD2 The average refractive index n of the first adhesive layer can be set to any appropriate value. AD1 and the average refractive index n of the second adhesive layer AD2 Can be adjusted to the average refractive index n of the resin film RF The difference satisfies the above relationship.
[0101] E-1. Adhesive layer
[0102] When the first adhesive layer and / or the second adhesive layer are adhesive layers, the first adhesive layer and the second adhesive layer can be formed by any suitable adhesive. As the specific example of adhesive, acrylic adhesive, rubber adhesive, silicone adhesive, polyester adhesive, urethane adhesive, epoxy adhesive, and polyether adhesive can be listed. By adjusting the type, quantity, combination and blending ratio of the monomers of the base resin forming the adhesive and the blending amount, reaction temperature, reaction time, etc. of the cross-linking agent, an adhesive with the desired characteristics corresponding to the purpose can be prepared. The base resin of the adhesive can only use one, or two or more can be used in combination. From the viewpoints such as transparency, processability and durability, acrylic adhesive (acrylic adhesive composition) is preferred.
[0103] The acrylic adhesive typically contains a (meth)acrylic polymer as a main component. The (meth)acrylic polymer may be contained in the adhesive in a proportion of, for example, 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more, in the solid content of the adhesive.
[0104] The (meth)acrylic polymer contains an alkyl (meth)acrylate as a monomer unit as a main component. In addition, (meth)acrylate refers to acrylate and / or methacrylate. The alkyl (meth)acrylate may be contained in the monomer component forming the (meth)acrylic polymer preferably in a ratio of 80% by weight or more, more preferably in a ratio of 90% by weight or more. As the alkyl group of the alkyl (meth)acrylate, for example, a linear or branched alkyl group having 1 to 18 carbon atoms can be cited. The average number of carbon atoms of the alkyl group is preferably 3 to 9, more preferably 3 to 6.
[0105] The acrylic adhesive may preferably contain a silane coupling agent and / or a crosslinking agent. As the silane coupling agent, for example, an epoxy-containing silane coupling agent may be cited. As the crosslinking agent, for example, an isocyanate crosslinking agent and a peroxide crosslinking agent may be cited. Furthermore, the acrylic adhesive composition may contain an antioxidant and / or a conductive agent. The details of the adhesive layer or the acrylic adhesive composition are, for example, described in Japanese Patent Publication No. 2006-183022, Japanese Patent Publication No. 2015-199942, Japanese Patent Publication No. 2018-053114, Japanese Patent Publication No. 2016-190996, and International Publication No. 2018 / 008712, and the records of these publications are cited in this specification as reference.
[0106] When the adhesive layer is an adhesive layer, the thickness of the adhesive layer can be set to any appropriate value. The thickness of the adhesive layer is preferably 1 μm to 10 μm, more preferably 2 μm to 8 μm, and further preferably 3 μm to 7 μm. When the thickness of the adhesive layer is within the above range, the adhesion of each component can be fully ensured. As described above, in one embodiment, the thickness of the adhesive layer can be adjusted in a manner such that the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is 12 μm to 40 μm.
[0107] E-2. Adhesive layer
[0108] When the first adhesive layer and / or the second adhesive layer is an adhesive layer, the adhesive layer can be formed of any appropriate adhesive. For example, an active energy ray-curable adhesive can be used. As the active energy ray-curable adhesive, any appropriate active energy ray-curable adhesive can be used, for example, an ultraviolet curable adhesive and an electron beam curable adhesive can be listed.
[0109] Active energy ray curing adhesives typically contain monofunctional components, multifunctional components (curing components) and photopolymerization initiators. The monofunctional components and multifunctional components are each typically free radical polymerizable compounds. As preferred monofunctional components, for example, higher alkyl esters of (meth) acrylic acid and modified bodies thereof can be listed. Specifically, isostearyl acrylate, lauryl acrylate, acryloyl morpholine, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, etc. can be listed. As preferred multifunctional components, for example, monomers and / or oligomers having more than two functional groups such as (meth) acrylate groups and (meth) acrylamide groups can be listed. Specifically, polyethylene glycol diacrylate, trimethylolpropane triacrylate, and glycerol triacrylate can be listed. As a specific example of a monofunctional component or a multifunctional component other than the above, tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxanediol diacrylate, EO modified diglycerol tetraacrylate, γ-butyrolactone acrylate, N-methylpyrrolidone, hydroxyethyl acrylamide, N-hydroxymethyl acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, 9-vinyl carbazole can be listed. In one embodiment, the monofunctional component or the multifunctional component has a ring structure. Specifically, acryloyl morpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, N-methylpyrrolidone, and 9-vinyl carbazole can be listed. The monofunctional component or the multifunctional component can be used only one kind, respectively, or two or more kinds can be used in combination.
[0110] The active energy ray-curable adhesive may further contain a cationic polymerizable compound as needed. The cationic polymerizable compound may be monofunctional or polyfunctional. As monofunctional cationic polymerizable compounds, for example, p-tert-butylphenyl glycidyl ether and 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane may be listed. As polyfunctional cationic polymerizable compounds, for example, 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane may be listed. As cationic polymerizable compounds, a silane coupling agent may be used. As a silane coupling agent, for example, 3-glycidoxypropyltrimethoxysilane may be listed.
[0111] The active energy ray-curable adhesive may further include any appropriate additive. For example, a plasticizer (such as an oligomer component), a cross-linking agent, a diluent, etc. may be listed. These additives may be used in any appropriate content according to the purpose. In one embodiment, the active energy ray-curable adhesive may further include an organic compound having an aromatic ring. If such a compound is used, the refractive index of the adhesive layer formed can be adjusted.
[0112] The details of the active energy ray-curable adhesive are described in, for example, Japanese Patent Application Laid-Open No. 2018-017996. The description of the publication is incorporated herein by reference.
[0113] The thickness of the adhesive layer is preferably 0.5 μm to 5 μm, more preferably 0.8 μm to 3 μm, and further preferably 1 μm to 2 μm. When the thickness of the adhesive layer is within the above range, the phase difference layer and the resin film can be appropriately adhered. As described above, in one embodiment, the thickness of the adhesive layer can be adjusted in such a way that the total thickness of the first adhesive layer, the resin film, and the second adhesive layer is 12 μm to 40 μm.
[0114] F. Image display device
[0115] The polarizer with a phase difference layer described in the above items A to E can be applied to an image display device. Therefore, an embodiment of the present invention includes an image display device using such a polarizer with a phase difference layer. As a representative example of an image display device, a liquid crystal display device and an electroluminescent (EL) display device (such as an organic EL display device, an inorganic EL display device) can be listed. The image display device of an embodiment of the present invention can have the above-mentioned polarizer with a phase difference layer on its visual recognition side. The polarizer with a phase difference layer can be stacked in a manner that the phase difference layer becomes the side of the image display unit (such as a liquid crystal unit, an organic EL unit, an inorganic EL unit) (in a manner that the polarizer becomes the visual recognition side). As described above, the polarizer with a phase difference layer of an embodiment of the present invention can suppress the generation of dents when it is attached to the image display panel. Therefore, the productivity of the image display device can be improved.
[0116] Example
[0117] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. The measuring methods of various properties are as follows. It should be noted that, unless otherwise specified, the "parts" and "%" in the examples and comparative examples are by weight.
[0118] (1) Thickness
[0119] The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics Co., Ltd., product name "MCPD-3000"), and the thickness exceeding 10 μm was measured using a digital micrometer (manufactured by Anritsu Co., Ltd., product name "KC-351C").
[0120] (2) Refractive index
[0121] (2-1) Adhesive layer and resin film
[0122] The pressure-sensitive adhesive layers formed in Examples and Comparative Examples and the resin films used in Examples were measured using an Abbe refractometer (manufactured by ATAGO Corporation, product name "DR-M 2 / 1550") at a measurement wavelength of 589 nm and a measurement temperature of 25°C.
[0123] (2-2) Adhesive layer
[0124] The adhesive used in the examples and comparative examples was coated on a cycloolefin polymer film (COP film) (thickness 100 μm), and the same COP film was attached to the coated surface, and visible light was irradiated using an active energy ray irradiation device to obtain a cured layer (monomer film). For the obtained cured layer, a prism coupler (manufactured by Cylon Technology, product name "SPA-4000") was used to measure the refractive index in the plane and the refractive index in the thickness direction, respectively, and their average value was taken as the average refractive index of the adhesive layer. The measurement wavelength was 594 nm and the measurement temperature was 23°C.
[0125] (3) Load resistance evaluation
[0126] The polarizer with a phase difference layer obtained in the embodiment and the comparative example is cut into 1 cm in length and 1 cm in width as a sample. The second adhesive layer of the sample is bonded to an aluminum reflector (Toray Advanced Film Co., Ltd., trade name "Cerapeel DMS-X42", total reflectivity: 86%). Then, the surface of the hard coating side of the sample is placed on a glass plate (Matsunami Glass Ind., Ltd., thickness: 0.7 mm) in such a way that the surface is in contact with the glass plate. Then, a weight is placed on a conical indenter (diameter 1.5 mm) through a polyethylene terephthalate (PET) sheet (Toray, thickness 80 μm) from the aluminum reflector side and pressed for 10 seconds. The weight (load) of the weight is changed to 300 g (1.7 MPa), 400 g (2.2 MPa) and 500 g (2.8 MPa) for measurement. Then, remove the weight and the pressure head, and observe the surface of the polarizer with a phase difference layer in contact with the glass plate at a polar angle of 30° to 60° visual azimuth to confirm the presence or absence of dents, and take the maximum load at which no dents can be confirmed as the load resistance. It should be noted that when the surface of the polarizer with a phase difference layer is set as the X-axis and the Y-axis, and the axis orthogonal to the XY plane is set as the Z-axis, the angle inclined from the Z-axis to the XY plane direction is set as the polar angle (θ), the MD direction of the polarizer used in the polarizer with a phase difference layer is set to 0°, and the measurement angle specified as counterclockwise relative to the MD direction of the polarizer is set as the azimuth (φ) for evaluation.
[0127] (4) Uneven interference
[0128] The polarizer with a phase difference layer obtained in the embodiment and the comparative example is bonded to a V3 reflector (manufactured by NEODIS) by means of the outermost adhesive layer. Then, an acrylic adhesive is applied to the polarizer side of the polarizer with a phase difference layer to form an adhesive layer with a thickness of 100 μm, and then a glass plate (manufactured by Matsunami Glass Ind., Ltd., thickness: 0.7 mm) is bonded by means of the formed adhesive layer. Then, the reflection is observed visually under a fluorescent lamp (three-wavelength tube) and evaluated according to the following benchmarks. The polar angle is 20° to 60° and the azimuth angle is observed for one week. It should be noted that the unevenness visually recognized under sunlight is not included in the interference unevenness.
[0129] ○ (good): No streaky or irregular unevenness due to interference light visually recognized as pink, green, or black was visually recognized.
[0130] △ (acceptable): Irregular unevenness due to interference light visually recognized as pink, green, and black is visually recognized, but no streak-like unevenness is visually recognized
[0131] × (room for improvement): Uneven streaks are visually recognized due to interference light that is visually recognized as pink, green, and black
[0132] (5) Reflection hue (hue at polar angle 45°)
[0133] The polarizer with phase difference layer obtained in the embodiment and comparative example was cut into 1 cm in length and 1 cm in width as a sample. The second adhesive layer of the sample was bonded to an aluminum reflector (Toray Advanced Film Co., Ltd., trade name "Cerapeel DMS-X42", total reflectivity: 86%). The case where there is a change in hue when observing the azimuth angle by reflection at a polar angle of 45° is set to 1, and the case where there is no change in hue is set to 2. Furthermore, the case where the hue is consistent with the azimuth angle even when observed at a polar angle of 0° is evaluated as 3.
[0134] (6)Judgment
[0135] The suitability as a polarizing plate with a retardation layer used in an image display device was evaluated based on the following criteria.
[0136] ○○ (best): 2.6Mpa or more in the load resistance test, interference unevenness is ○ (good), and reflection color is 3
[0137] ○ (good): 2.0 MPa or more in the load resistance test, interference unevenness is ○ (good), and reflection hue is 2 or 3
[0138] △ (acceptable): 2.0Mpa or more in the load resistance test, the interference unevenness is △ (acceptable) or ○ (good), and the reflection color is 1, 2 or 3
[0139] × (room for improvement): Less than 2.0 MPa in the load resistance test, or the interference unevenness is × (room for improvement), or the reflection color is 1
[0140] [Manufacturing Example 1] Preparation of Adhesive Composition
[0141] 1. Preparation of base polymer
[0142] A monomer mixture containing 94.9 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA), and 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) was placed in a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Next, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with ethyl acetate relative to 100 parts by weight of the monomer mixture (solid content), and nitrogen was introduced while slowly stirring to replace the nitrogen atmosphere. The liquid temperature in the flask was maintained at around 55°C and a polymerization reaction was performed for 7 hours. Then, ethyl acetate was added to the obtained reaction solution to obtain a solution of a (meth)acrylic acid polymer with a weight average molecular weight of 2 million adjusted to a solid content concentration of 30%.
[0143] 2. Preparation of acrylic adhesive composition
[0144] An acrylic adhesive composition was prepared by adding 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / toluene diisocyanate adduct, manufactured by Tosoh Corporation, trade name "CORONATE L") and 0.1 parts by weight of a silane coupling agent (trade name: KBM 403, manufactured by Shin-Etsu Chemical Co., Ltd.) to 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution.
[0145] [Manufacturing Example 2] Preparation of Adhesive 1
[0146] 50 parts by weight of a caprolactone derivative (manufactured by Daicel, trade name "PLACCEL FA1DDM"), 40 parts by weight of acryloylmorpholine (ACMO: registered trademark, manufactured by Kojin Co., Ltd.), 10 parts by weight of an acrylic polymer (manufactured by Toagosei Co., Ltd., trade name "ARFON UP-1190"), 3 parts by weight of a photopolymerization initiator 1 (manufactured by Nippon Kayaku Co., Ltd., trade name "KAYACURE DETX-S"), and 3 parts by weight of a photopolymerization initiator 2 (manufactured by BASF Japan, trade name "IRGACURE 907") were mixed to prepare an adhesive 1. The obtained adhesive 1 was photocured (300 mJ / cm 2 ) and the average refractive index of the cured product obtained is 1.51.
[0147] [Manufacturing Example 3] Preparation of Adhesive 2
[0148] 60 parts by weight of fluorene acrylate (manufactured by Osaka Gas Chemicals Co., Ltd., trade name "OGSOL EA-F5710"), a caprolactone derivative (manufactured by Daicel, trade name "PLACCEL FA1DDM"), 20 parts by weight of acryloylmorpholine (manufactured by KJ Chemicals, trade name "ACMO"), 5 parts by weight of ARFON UP-1190 (manufactured by Toagosei Co., Ltd.), 1 part by weight of photopolymerization initiator 1 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, manufactured by IGM Resins BV, trade name "Omnirad 819"), 2 parts by weight of photopolymerization initiator 2 (1-hydroxycyclohexyl phenyl ketone, trade name "Omnirad 184", manufactured by IGM Resins BV), 2 parts by weight of diethylthioxanthone (manufactured by Nippon Kayaku Co., Ltd., trade name "KAYACURE DETX-S”) was stirred at 50°C for 1 hour to prepare an adhesive 2. The obtained adhesive 2 was photocured (300 mJ / cm 2 ) and the average refractive index of the cured product obtained is 1.57.
[0149] [Example 1]
[0150] <Production of polarizing plate>
[0151] 1. Preparation of polarizer
[0152] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.
[0153] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1, and the resulting substance was dissolved in water to prepare a PVA aqueous solution (coating liquid).
[0154] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.
[0155] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).
[0156] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0157] Next, the film was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so that the single body transmittance (Ts) of the polarizer finally obtained would be a desired value (dyeing treatment).
[0158] Next, the sample was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0159] Then, while the laminate is immersed in an aqueous boric acid solution (boric acid concentration 4 wt%, potassium iodide concentration 5 wt%) at a liquid temperature of 70°C, it is uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different peripheral speeds so that the total stretching ratio becomes 5.5 times.
[0160] Then, the laminated body was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).
[0161] Thereafter, the film was dried in an oven maintained at approximately 90° C. while being brought into contact with a SUS heating roll maintained at a surface temperature of approximately 75° C. (drying shrinkage treatment).
[0162] In this manner, a polarizer having a thickness of 6 μm was formed on the resin substrate to obtain a polarizing plate having a structure of resin substrate / polarizer. The single-body transmittance Ts of the polarizer was 43.3%.
[0163] 2. Preparation of polarizer
[0164] On the surface of the obtained polarizer (the surface on the opposite side to the resin substrate), a HC-COP film is bonded with an ultraviolet curing adhesive. It should be noted that the HC-COP film is a film having an HC layer (thickness 4 μm) formed on a cycloolefin resin (COP) film (thickness 25 μm), and is bonded in such a way that the COP film becomes the polarizer side. It should be noted that the Re (550) of the COP film is 135 nm. Next, the resin substrate is peeled off, and a triacetyl cellulose (TAC) film (thickness 20 μm) is bonded to the peeled surface with the aid of an ultraviolet curing adhesive. As described above, a polarizer having the structure of HC layer / COP film (protective layer) / polarizer / TAC film (protective layer) is obtained.
[0165] 3. Preparation of polarizing film with phase difference layer
[0166] 10 g of a polymerizable liquid crystal showing a nematic liquid crystal phase (manufactured by BASF: trade name "Paliocolor LC 242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: trade name "Irgacure 907") were dissolved in 40 g of toluene to prepare a liquid crystal composition (coating liquid).
[0167]
[0168] The surface of the PET film (thickness 38 μm) was rubbed with a rubbing cloth to perform an orientation treatment. The orientation treatment direction was set to be 15° relative to the absorption axis of the polarizer when attached to the polarizing plate when observed from the visual recognition side. The above-mentioned liquid crystal coating liquid was applied to the orientation treatment surface using a rod coater and heated and dried at 90°C for 2 minutes to orient the liquid crystal compound. The liquid crystal layer thus formed was irradiated with 100 mJ / cm using a metal halide lamp. 2 The liquid crystal layer is cured by light, thereby forming a liquid crystal orientation solidification layer, i.e., a first phase difference layer, on the PET film. The first phase difference layer has a thickness of 2 μm and an in-plane phase difference Re (550) of 270 nm. Furthermore, the first phase difference layer has a refractive index distribution of nx>ny=nz.
[0169] The adhesive obtained in Production Example 2 was applied to the TAC film-side surface of the polarizing plate obtained above, and the first retardation layer obtained above was bonded thereto via an adhesive layer having a thickness of 1 μm. Next, the PET film was peeled off from the first retardation layer.
[0170] In addition, a second phase difference layer was formed on the PET film in the same manner as above, except that the coating thickness was changed and the orientation treatment direction was made 75° relative to the absorption axis of the polarizer when viewed from the visual recognition side. The thickness of the second phase difference layer was 1 μm, and the in-plane phase difference Re (550) was 140 nm. Furthermore, the second phase difference layer had a refractive index distribution of nx>ny=nz.
[0171] The adhesive obtained in Manufacturing Example 1 is applied to the release surface of the PET film of the first phase difference layer to form an adhesive layer (first adhesive layer) with a thickness of 5 μm, and a TAC film (manufactured by Konica Minolta, with a thickness of 20 μm and an average refractive index of 1.49) is bonded. Similarly, the adhesive obtained in Manufacturing Example 1 is applied to the surface of the TAC film that is not in contact with the first phase difference layer to form an adhesive layer (second adhesive layer) with a thickness of 5 μm, and the surface of the second phase difference layer obtained above that is not laminated with the PET film is bonded. Next, the PET film is peeled off from the second phase difference layer, and the adhesive obtained in Manufacturing Example 1 is applied to the release surface to form an adhesive layer with a thickness of 25 μm, thereby obtaining a polarizer with a phase difference layer. It should be noted that, until the evaluation, a polyethylene terephthalate film (PET film, diaphragm) with a thickness of 38 μm treated with a silicone release agent is bonded to the second adhesive layer. The results are shown in Table 1.
[0172] [Example 2]
[0173] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1 except that the first adhesive layer and the second adhesive layer were adhesive layers having a thickness of 1 μm formed using the adhesive 1 obtained in Production Example 2. The results are shown in Table 1.
[0174] [Example 3]
[0175] A polarizing plate with a retardation layer was obtained in the same manner as in Example 2 except that a cyclic olefin resin film (manufactured by ZEON Corporation, trade name “ZEONOR FILM ZF14”, thickness 13 μm, average refractive index 1.52) was used instead of the TAC film.
[0176] [Example 4]
[0177] A polarizing plate with a retardation layer was obtained in the same manner as in Example 3 except that the adhesive 2 obtained in Production Example 3 was used instead of the adhesive 1 obtained in Production Example 2. The results are shown in Table 1.
[0178] [Example 5]
[0179] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1 except that a cyclic olefin resin film (manufactured by ZEON Corporation, trade name “ZEONOR FILM ZF14”, thickness 13 μm, average refractive index 1.52) was used instead of the TAC film.
[0180] (Comparative Example 1)
[0181] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1 except that the first retardation layer and the second retardation layer were laminated via an adhesive layer (15 μm thick) formed using the adhesive obtained in Production Example 1 without laminating the resin film.
[0182] (Comparative Example 2)
[0183] In the preparation of the polarizing plate, a polarizing plate with a phase difference layer was obtained in the same manner as in Example 1, except that no TAC film was attached to the polarizer, no resin film was laminated, and the first phase difference layer and the second phase difference layer were laminated via an adhesive layer (thickness 1 μm) formed using the adhesive 1 obtained in Production Example 2. The results are shown in Table 1.
[0184] [Table 1]
[0185]
[0186] [evaluate]
[0187] As can be seen from Table 1, the polarizing plates with retardation layers according to the examples of the present invention suppress the occurrence of interference unevenness and pits.
[0188] Industrial Applicability
[0189] The polarizing plate with a retardation layer according to the embodiment of the present invention can be suitably used in image display devices such as liquid crystal display devices, organic EL display devices, and inorganic EL display devices.
Claims
1. A polarizing plate with a phase difference layer, which comprises, in order: a polarizing plate including a polarizer, an orientation solidified layer of a liquid crystal compound, namely a first phase difference layer, a resin film, and an orientation solidified layer of a liquid crystal, namely a second phase difference layer, The slow axis of the first phase difference layer intersects with the slow axis of the second phase difference layer. The slow axis of the first phase difference layer intersects with the absorption axis of the polarizer, The thickness of the resin film is 10 μm to 30 μm.
2. The polarizing plate with a phase difference layer according to claim 1, wherein: The resin film is laminated on the first phase difference layer via a first adhesive layer. The average refractive index n of the first adhesive layer AD1 The average refractive index n of the resin film RF The following relations are satisfied: -0.03<n AD1 -n RF <0.05。 3. The polarizing plate with a phase difference layer according to claim 1, wherein: The resin film is laminated on the second phase difference layer via a second adhesive layer. The average refractive index n of the second adhesive layer AD2 The average refractive index n of the resin film RF The following relations are satisfied: -0.03<n AD2 -n RF <0.05。 4. The polarizing plate with a phase difference layer according to claim 1, wherein: The resin film is laminated on the first phase difference layer via a first adhesive layer. The resin film is laminated on the second phase difference layer via a second adhesive layer. The total thickness of the first adhesive layer, the resin film, and the second adhesive layer is 12 μm to 40 μm.
5. The polarizing plate with a phase difference layer according to claim 1, wherein: The resin film is a cyclic olefin resin film or a cellulose resin film.
6. The polarizing plate with a phase difference layer according to claim 1, wherein: The resin film has a refractive index distribution of nx=ny>nz.
7. The polarizing plate with a phase difference layer according to claim 1, wherein: The Re (550) of the first phase difference layer is 200 nm to 300 nm, and the angle between the slow axis of the first phase difference layer and the absorption axis of the polarizer is 10° to 20°. The Re (550) of the second phase difference layer is 100 nm to 190 nm, and the angle formed by the slow axis of the second phase difference layer and the absorption axis of the polarizer is 70° to 80°.
8. The polarizing plate with a retardation layer according to any one of claims 2 to 4, wherein The adhesive layer is an adhesive layer. 9 . An image display device comprising the polarizing plate with a retardation layer according to claim 1 . 10 . The image display device according to claim 9 , which is an organic electroluminescent display device. 11 . An image display device comprising the polarizing plate with a phase difference layer according to claim 8 . 12 . The image display device according to claim 11 , which is an organic electroluminescent display device.
Citation Information
Patent Citations
Liq. crystalline (LC) material
DE19504224A1
Novel polymerizable liquid crystalline compounds
DE4408171A1
Liquid crystalline reticulated polysiloxanes
EP0066137A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups
EP0358208A2